Morphological Characteristics and Changes in Chemical Properties of Sandy Soil Under Chili Plants in Erosion-prone Areas, Ternate, Indonesia - Aji, Krishna; Hartati, Tri Mulya; Arifin, Tarisa Jasmine; Utami, Kartika (TERRA : Journal of Land Restoration, 2025)
Sandy soils are characterized by their loose texture, low water-holding capacity, and generally low organic matter content, all of which significantly influence soil chemical properties. Soil chemistry serves as a critical indicator of soil fertility and directly affects plant productivity. This study aimed to analyze both the morphological characteristics and the changes in chemical properties of sandy soils cultivated with chili plants in erosion-prone areas. A descriptive quantitative method was employed, with soil samples collected before planting and after harvest. Sampling followed the standards outlined in the USDA Field Book for Describing and Sampling Soils. The chemical parameters analyzed included soil pH (H₂O), soil organic carbon, total nitrogen, available phosphorus (P₂O₅), and potassium (K₂O). The results indicated measurable changes in all tested soil chemical properties. The sandy soils in the study area were clas sified as Inceptisols, distinguished by horizon differentiation observed in the subsoil layer. Post-harvest analysis revealed increases in organic carbon, total nitrogen, and available phosphorus levels, while pH and potassium concentrations decreased. These findings suggest that agricultural activity in erosion-prone sandy soils can influence nutrient dynamics, potentially supporting sustainable vegetative conservation practices. Appropriate land management strategies—such as the incorporation of organic matter, implementation of terracing, and adoption of agroforestry systems are strongly recommended to mitigate soil degradation and enhance agricultural productivity. Furthermore, this study supports the objectives of Sustainable Development Goal’s (SDGs) 15, which advocates for sustainable land use to combat soil degradation and promote ecosystem resilience.